2013
DOI: 10.1111/jonm.12173
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and the older nurse

Abstract: To prevent bullying, initiatives that recognise the skills and knowledge that nurses contribute to patient care need to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 50 publications
(73 reference statements)
1
33
1
Order By: Relevance
“…maintain that among nurses bullying can be present in all ages given that many hospitals are oppressive hierarchical structures with risk for horizontal violence . It is unfortunate if bullying becomes a norm at the workplace, when neither younger nor older nurses recognise or do not dare to deal with the problem . In our study, there was also a significant difference in the reported experience of bullying between respondents born in Sweden and those born in another country.…”
Section: Discussionmentioning
confidence: 53%
“…maintain that among nurses bullying can be present in all ages given that many hospitals are oppressive hierarchical structures with risk for horizontal violence . It is unfortunate if bullying becomes a norm at the workplace, when neither younger nor older nurses recognise or do not dare to deal with the problem . In our study, there was also a significant difference in the reported experience of bullying between respondents born in Sweden and those born in another country.…”
Section: Discussionmentioning
confidence: 53%
“…However, other studies have demonstrated that bullying often affects more than the novice nurse (Dewitty et al 2009;Etienne 2014). Older nurses may display increased competence, initiative and personal strength, and sets the stage for being bullied by younger nurses (Longo 2013). Conversely, physical limitations accompanied by an accelerated work pace also targets older nurses for bullying (Longo 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Older nurses may display increased competence, initiative and personal strength, and sets the stage for being bullied by younger nurses (Longo ). Conversely, physical limitations accompanied by an accelerated work pace also targets older nurses for bullying (Longo ). In this study, nurses reported that they had worked for a full decade before the bullying occurred.…”
Section: Discussionmentioning
confidence: 99%
“…, Franz et al . , Ahmed , Longo ). Researchers have estimated that about 80% of incidents go unreported either because managers are unwilling to defend staff nurses from aggressive or abusive behaviours or because nurses are reluctant to report these situations for fear of blame, losing their job, lack of confidentiality or lack of information about where to get help (Rosenstein 2001, Gacki‐Smith et al .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the reporting of disruptive/abusive situations to hospital/management was not assessed, making conclusions difficult. However, several earlier studies have attributed under-reporting of abuse to managers/supervisors to unsupportive attitudes (Gacki-Smith et al 2009, Franz et al 2010, Ahmed 2012, Longo 2013. Researchers have estimated that about 80% of incidents go unreported either because managers are unwilling to defend staff nurses from aggressive or abusive behaviours or because nurses are reluctant to report these situations for fear of blame, losing their job, lack of confidentiality or lack of information about where to get help (Rosenstein 2001, Gacki-Smith et al 2009, Franz et al 2010, Longo 2013.…”
Section: Discussionmentioning
confidence: 99%